Adoption of Cash on Delivery Payment Method in E-commerce Shopping: A Value-based Adoption Model Approach - Lidya Veronica Christy Rihidima; Yusri Abdillah; Anni Rahimah (Universitas Airlangga, 2022)
Objectives: To examine what factors can influence adoption intention through perceived value and how much influence compatibility can have on the relationship between perceived value and adoption intention. Furthermore, through the results of this research, it is hoped that local retailers can create new services that are appropriate and can help consumers. Design/Method/Approach: Existing scales are adapted, and the field study is conducted in seven different cities of East Java Province, Indonesia. Based on purposive sampling, 195 respondents in seven telecommunication retail outlets completed a questionnaire related to cash-on-delivery service as a payment method of Topsell. This national telecommunication retailer adopts cash on delivery as their payment method. One hundred fifty-four qualified questionnaires are eventually used for data analysis. Furthermore, this study utilizes explanatory research with quantitative research methods. The sample collection method uses a purposive sampling method. Findings: The research results obtained, it can be concluded that all the hypotheses proposed in this study can be accepted. Therefore, these results show that the COD service offered by Topsell can provide technical convenience. Furthermore, compatibility can strengthen the relationship between perceived value and adoption intention. Originality: Many studies utilize the theory of value-based adoption models, but only a few include the compatibility variable as a moderating variable. This research offers originality, especially in service innovation research. The researcher believes compatibility effectively strengthens the relationship between perceived value and adoption intention. Practical/Policy Implications: The research results are expected to contribute ideas. This research develops the theory of the value-based adoption model. Further researchers can adopt the research model and framework. Through all the results obtained, it can provide benefits for local retailers to survive amid this tight business competition by paying attention to the attributes of the value-based adoption model and the suitability of services with community trends. It is also recommended that Topsell and other telecommunication retail companies create a friendly web so that there is a good assessment of the COD services offered to consumers.